National Minorities – Constitutional Status, Rights and Protection - Kohecz, Tamás (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
National minorities and their status, rights and protection are among most sensible and disputed political issues all over Central and Eastern Europe (CEE). All eight analysed nation states constitutionally recognise national minorities and at least some group-specific minority rights. The list of constitutional group-specific minority rights varies, and it is longest in Serbia, Slovenia and Romania; however, national legislators in all states have wide discretion to regulate these constitutional rights and to determine their scope and content with laws. The constitutionally protected minorities are named only in Slovenia and Croatia, and constitutions only exceptionally make difference between minorities based on territoriality or numerical concentration. The jurisprudence of constitutional courts generally reveals no particular judicial activism in this area – with the exception of the Constitutional Court of Slovenia – and courts have usually failed to conceptualise minority rights and made no proper equilibrium between minority rights and constitutional provisions protecting and promoting the nation state and dominant position of the titular nation. Furthermore, in some states, the status of minorities is tacitly still more a state security issue and less a constitutional law question.KEYWORDS: National minorities, titular-dominant nations, constitution, group-specific minority rights, nation state building, equality.